PERGESERAN FUNGSI DAN TERITORIALITAS PADA RUANG RUMAH ADAT CIKONDANG - Annisaa Kurnia W.; Imam Santosa (Serat Rupa: Journal of Design, 2021)
The use of the functions of spaces in Cikondang Traditional House has changed since 1980 by the government as a cultural heritage. This place was established as a cultural heritage since indigenous peoples and traditional leaders tried to open themselves up to the outside. Cikondang Traditional House was original house for the family of the traditional leader and now become a cultural heritage to remain the legacy as a symbolic physical legacy for the existence of the traditional village. As time goes by, the activities have a change in function, such as deliberation activities for local people, the tourists and traditional rituals. All of these activities are routinely carried out in Cikondang Traditional Village. The Traditional house as a function for conducting customary deliberation, tourist visits, and ritual celebrations was carried out as a form of respect for ancestors and outsiders who always visit this place. All of the activities that take place in traditional house spaces has become a form of change in interaction between users and territories, thus this research aims to determine the shift in past and present, to determine changes in spatial territory ang the factors become territoriality. This research is a descriptive analysis using a phenomenological approach which can be seen a fact that occurs in a shift in function, a change in the territorial zone and the factors that make up the territoriality itself. This research analyzed using four steps that commonly used in phenomenology. The territory theory by Hall and Altman used in the analysis of territorial change which begins with a function shift, while the theory forward by Brower also used as a theory that strengthens territoriality in spaces. The result showed that not only the function shift, social cohesiveness, interaction between the users and defensive mechanisms that make the space territories in a traditional house change, but there are protocols or customary rules that must be obeyed as a respect sign and traditional rituals